What is the meaning of PASAT rejection in multiple sclerosis?. (12th April 2019) - Cortés‐Martínez, Ana; Matias‐Guiu, Jordi A.; Pytel, Vanesa; Montero, Paloma; Moreno‐Ramos, Teresa; Matías‐Guiu, Jorge
Abstract : Background: Paced Auditory Serial Addition Test (PASAT) is one of the most used neuropsychological tests in multiple sclerosis (MS), specially for screening. However, the applicability of the test is limited because of the rejection of the test completion in a proportion of patients. We aimed to investigate the clinical, neuropsychological, and MRI findings associated to PASAT rejection. Methods: Cross‐sectional and observational study. A total of 343 patients with MS underwent neuropsychological testing and structural MRI. Results: One hundred and twenty‐one (35.3%) of patients declined the administration of the test. Among those patients that declined the administration, rejection occurred before the onset of test in 35.5%, during or after the practice in 43%, and during the test administration in 21.5%. Rejection of the test was associated to a worse performance in all cognitive tests administered, but not to depression or baseline fatigue scales. In regression analysis, education, cognitive impairment, EDSS, and white matter lesion load were independently associated to rejection of the test. Conclusions: Paced Auditory Serial Addition Test rejection is associated with a higher probability of cognitive impairment in MS. This suggests that patients that reject the administration of PASAT should be further examined with a neuropsychological battery to evaluate the possibility of cognitive dysfunction.